HUBUNGAN PEMBELAJARAN TUTORIAL DENGAN MOTIVASI BELAJAR MAHASISWA TINGKAT II PROGRAM STUDI S1 KEPERAWATAN SEKOLAH TINGGI ILMU KESEHATAN STELLA MARIS MAKASSAR - Henny Pongantung (Jurnal Keperawatan Florence Nightingale, 2018)
Learning tutorials based on the concept of independent study seeks to trigger and stimulate the self-reliance, discipline and self-initiatives of students, so that students can be motivated in learning or attending. The purpose of this research is to know the relationship of the learning motivation of students learning tutorial with level II Courses Undergraduate nursing STIK Stella Maris Makassar. This research uses the draft research korelasional croos-sectional approach. Sampelnya is a student level II Courses Undergraduate nursing STIK Stella Maris totalling 98 students. Sampling is done using the technique of Nonprobability Sampling the sampling approach saturation. Questionnaire used for data collection. Data was analyzed using chi square test alternative test with Continuity Correction using program SPSS for windows version 5. Test result statistics retrieved value X 2 = count = X2tabel > 5.965 3.841 so that it can be concluded that there is a relationship of learning motivation of students learning tutorial with level II Degree program nursing health science high school Stella Maris Makassar. There are a variety of learning applied in lectures, one of which learning tutorials that can increase students ' learning motivation, therefore researchers suggested that institutions pay more attention to the availability of facilities used in the learning process so that the process of learning tutorials tutorials can take place with better in the future.